2022
DOI: 10.1021/acs.jmedchem.1c02141
|View full text |Cite|
|
Sign up to set email alerts
|

Discovery of AZD4831, a Mechanism-Based Irreversible Inhibitor of Myeloperoxidase, As a Potential Treatment for Heart Failure with Preserved Ejection Fraction

Abstract: Myeloperoxidase is a promising therapeutic target for treatment of patients suffering from heart failure with preserved ejection fraction (HFpEF). We aimed to discover a covalent myeloperoxidase inhibitor with high selectivity for myeloperoxidase over thyroid peroxidase, limited penetration of the blood–brain barrier, and pharmacokinetics suitable for once-daily oral administration at low dose. Structure–activity relationship, biophysical, and structural studies led to prioritization of four compounds for in-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 47 publications
0
21
0
Order By: Relevance
“…Long-term human studies with MPO inhibitors have not been carried out to date. In phase I studies, once-daily single, and multiple ascending dosing of AZD4831 (a 2-thioxanthine-based MPO inhibitor like AZM198) in healthy volunteers was generally well tolerated [ 20 ]. From a clinical perspective, most patients with MPO deficiency are asymptomatic, with severe (candida) infectious complications occurring only occasionally in the setting of comorbid diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Long-term human studies with MPO inhibitors have not been carried out to date. In phase I studies, once-daily single, and multiple ascending dosing of AZD4831 (a 2-thioxanthine-based MPO inhibitor like AZM198) in healthy volunteers was generally well tolerated [ 20 ]. From a clinical perspective, most patients with MPO deficiency are asymptomatic, with severe (candida) infectious complications occurring only occasionally in the setting of comorbid diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
“…We observed that in that model, MPO activity was higher in unstable than stable plaque, and that genetic or pharmacological blockade of MPO activity attenuated the formation of unstable plaque [ 18 ]. Importantly, the MPO suicide inhibitor used (AZM198) [ 19 , 20 ] decreased plaque MPO activity and plaque instability without affecting circulating leukocytes and lipids, lesion macrophages, MPO protein and lipids [ 18 ]. These findings raise the possibility of stabilizing vulnerable plaque via the therapeutic inhibition of arterial MPO activity.…”
Section: Introductionmentioning
confidence: 99%
“…Radiolabeled 14 C-AZD4831 (Fig. 1) was manufactured by Pharmaron (Rushden, UK) following the procedure described previously (Inghardt et al, 2022). The solid material was isolated following crystallization from ethanol and water.…”
Section: Chemicals Reagents and Equipmentmentioning
confidence: 99%
“…AZD4831 -(R)-1-(2-(1-aminoethyl)-4-chlorobenzyl)-2-thioxo-2,3-dihydro-1Hpyrrolo [3,2-d]pyrimidin-4(5H)-one -is a novel, covalent MPO inhibitor with high selectivity for MPO at low oral doses (Inghardt et al, 2022). In Phase I studies in healthy volunteers, AZD4831 was rapidly absorbed with a long plasma half-life, This article has not been copyedited and formatted.…”
Section: Introductionmentioning
confidence: 99%
“…Thioxanthines are a class of suicide substrates that irreversibly inactivate MPO through modification of its heme groups and thereby inhibit HOCl production [20]. They have already passed phase I clinical trials and are currently being investigated in phase II studies in HF with preserved ejection fraction (NCT03756285) [21,22]. Further preclinical studies have shown beneficial effects of MPO inhibition on atherosclerotic plaque stability and pulmonary vascular function [23][24][25].…”
Section: Introductionmentioning
confidence: 99%